Design and Implementation of a smart monitoring system of a modern renewable energy micro-grid system using a low-cost data acquisition system and LabVIEWTM program - Nutthaka Chinomi; Monthon Leelajindakrairerk; Suttipong Boontaklang; Chow Chompoo-Inwai (My University, 2017)
This paper focuses on designing and implementing a prototype of smart monitoring system capable of doing multi functions i.e. monitoring, analysing and communicating with devices in a small micro-grid system. This research proposes the use of a combination between a low-cost data acquisition (NI compact DAQ) device and a commercially-used LabVIEW™ program in being a smart renewable monitoring and analysing system. The proposed set of equipment is capable of doing all the functions needed by utilities and users in the aforementioned micro-grid system. The proposed prototype is capable of measuring, monitoring and recording in both normal system operating conditions and when faults occurred. A number of power quality parameters that can be monitored and analysed are as follows: voltage (V), current (I), real power (P), reactive power (Q), apparent power (S), energy consumption (kWhr), power factor (PF), harmonics distortion (THDi and THDv), over/under voltage, sag as well as swell. Extensively in this paper, the principle design concepts, hardware implementations, the LabVIEWTM algorithm, how the overall system works, experimental results, the accuracy verification process and the conclusions will be thoroughly elaborated.
Keywords: Implementation; Photovoltaic System Optimization Techniques